EVALUASI PENERAPAN AKUNTANSI PENERIMAAN DANA TRANSFER PADA BADAN PENGELOLA KEUANGAN DAN BARANG MILIK DAERAH PROVINSI SULAWESI UTARA - Wantah, Indah Helda; Saerang, David P.E.; Mawikere, Lidia (Universitas Sam Ratulangi, 2015)
Each SKPD who has the task of picking and receiving local revenue collection and acceptance shall perform under the terms set out in the legislation. The purpose of this study was to determine the application of accounting receipt of funds transfer in Financial Management Board and Regional Property North Sulawesi Province. Accounting receipt of funds transfer includes a series of activities of receiving, recording, distribution and accountability in the management of money that is the Regional Finance Management Unit (SKPKD) and / or Unit (SKPD). The method used is descriptive qualitative. Based on this study, the obtained results that the Financial Management Board and Regional Property North Sulawesi receive funds transfers from the center, are recorded in the form of journal and distribution in accordance with applicable regulations, and accountability made in the financial statements. However, the Financial Management Board and Regional Property North Sulawesi need to improve the understanding of the technical terms for each employee.